2018
DOI: 10.1016/j.chb.2017.11.019
|View full text |Cite
|
Sign up to set email alerts
|

“Technoference” and implications for mothers' and fathers' couple and coparenting relationship quality

Abstract: Technology devices are widely used today, creating opportunities to connect and communicate with distant others while also potentially disrupting communication and interactions between those who are physically present (i.e., technoference or phubbing). These disruptions in couple and coparenting relationships have the potential to negatively impact relationship outcomes. In this two-part study of 182 married/cohabiting couples from the Daily Family Life Project and 239 couples from the Couple Well-Being Projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 61 publications
4
92
1
3
Order By: Relevance
“…Not only is distraction linked with parenting behaviors, but it is also linked with family interactions and relationship quality. Researchers in the literature on technoference —or the everyday intrusions and interruptions of devices in our face‐to‐face interactions (McDaniel & Coyne, )—have found that parents perceive technology interruptions happening in their interactions with their romantic partners, with their children, and in their parenting and coparenting interactions (McDaniel & Coyne, , ; McDaniel, Galovan, Cravens, & Drouin, ; McDaniel & Radesky, , ). Not only are these interruptions happening, but more frequent interruptions are connected with perceptions of lower quality couple and coparenting relationships.…”
Section: How Does This Use Impact Parents and Parenting?mentioning
confidence: 99%
“…Not only is distraction linked with parenting behaviors, but it is also linked with family interactions and relationship quality. Researchers in the literature on technoference —or the everyday intrusions and interruptions of devices in our face‐to‐face interactions (McDaniel & Coyne, )—have found that parents perceive technology interruptions happening in their interactions with their romantic partners, with their children, and in their parenting and coparenting interactions (McDaniel & Coyne, , ; McDaniel, Galovan, Cravens, & Drouin, ; McDaniel & Radesky, , ). Not only are these interruptions happening, but more frequent interruptions are connected with perceptions of lower quality couple and coparenting relationships.…”
Section: How Does This Use Impact Parents and Parenting?mentioning
confidence: 99%
“…The third section reviews literature on potential consequences of the mismatch (Panels D and E in Figure 1). Here we focus narrowly on the topic of technoference, defined as the ways in which smartphone use may interfere with or intrude into everyday social interactions, either between couples or within families (McDaniel & Coyne, 2016;McDaniel, Galovan, Cravens, & Drouin, 2018;McDaniel & Radesky, 2018). This section also includes coverage of the ways in which smartphone use may also disrupt basic cognitive processes needed to maintain intimacy.…”
mentioning
confidence: 99%
“…The relationship between DSI and digital education is strategic, since digital education is essential to create DSI applications. Furthermore, digital education is also necessary to mitigate the disadvantages and negative effects that the development of technology can produce (Elhai, Levine, Dvorak, & Hall, 2016;Delpechitre, Black, & Farrish, 2018;Kim, 2017;Rotondi, Stanca, & Tomasuolo, 2017), including technoference, the everyday disturbances in interaction between partners caused by technology (McDaniel & Galovan, 2018).…”
Section: Figure 2 the Process Of Social Innovationmentioning
confidence: 99%